Imbibing Water in Questing Ticks - Beals, Brendan; Haman, Colter; Park, Yoonseong (My University, 2017)
Although some ticks are known to stick to a host for the entirety of their life, some are known to drop off of their host after feeding to take time to molt. Of those who drop off of their host, some have been observed to drink water. However, it is unknown whether all species of tick drink water, and if they do, in the same way as each other. Our goal was to look into which species drink water, their drinking patterns, and how they might be drinking differently from each other. Our results showed that ticks appear to continue drinking as a semi-steady pace up to one hour as long as water is available for them to drink. Minimal differences were traceable through the experiment performed. Our research could lead to better understanding of a tick’s natural behavioral patterns and further add to our knowledge of their biology, which can add to information that could pertain to their being a vector species.